In Search of an Unknown Address in European Union Civil Proceedings - Vaicekauskas, Vytautas (Teisė, 2025)
This article analyses the novelty established in Article 7 of the EU Service Regulation – assistance in determining the address of the addressee, seeking to ensure right to fair trial. The article examines how this innovation of the Regulation affects the strengthening of procedural safeguards. It examines the concept of unknown address, its origins and the circumstances of its establishment. The paper points out that the new assistance mechanism extends the scope of the Regulation by providing administrative assistance, access to databases and disclosure of information in determining the unknown address. However, it is critically pointed out that some of the innovations have been abandoned in the legislative process without any ground.
Keywords: service of documents; unknown address; assistance in address enquiries; EU Service Regulation; European Union civil procedure